Pola Pertumbuhan Dan Kebiasaan Makan Ikan Janggut (Esomus metallicus) Di Sungai Ogan Sumatera Selatan - Rosanti, Dewi; Mutiara, Dian; Maryani, Sri (Indobiosains, 2024)
ABSTRACT Research on the growth patterns and eating habits of bearded fish (Esomus metallicus) in the Ogan River was carried out in April-May 2024. This research aims to study the growth patterns of bearded fish and analyze the types of food of bearded fish that live in the Ogan River, Palembang City. The research uses a survey method. Sampling was carried out at 3 stations. Station I is around water vegetation or is a natural habitat for fish, station II is around residential areas and station III is around a rubber factory. The fish obtained were taken as samples from 5 individuals each from each station. Each fish was measured for total length and weight. The sample was then dissected, the stomach was taken. The contents of the stomach are examined to see the composition of the types of food, and measure the total volume of food eaten and the volume of each type of food to determine the largest type of food (Index of Preponderance). The research results showed that the composition of the jangut fish's food was phytoplankton (44.39%), leaf debris (27.26%), zooplankton (0.26%) and unidentified (28.07%). The growth pattern of beard fish is negative allometric or growth in length is faster than growth in weight. Keywords: Esomus metallicus, Index of Preponderance, allometric